A comparison study between vessel sealing technique and conventional (Milligan Morgan) excisional hemorrhoidectomy - Ahire, Manoj Kumar D.; Rathod, Chetan M.; Baghadia, Samir; Nandu, Bharat (International Surgery Journal, 2016)
Background: Excisional hemorrhoidectomy including the Milligan-Morgan technique and its modification has been the most widely used and effective procedure for grade 3 and grade 4 hemorrhoids. But due its complications attempts were made to modify these conventional approaches by using different techniques or tools to decrease blood loss, and reduce operating time and postoperative analgesic requirement. The aim of the present study was to compare vessel sealing technique with conventional Milligan Morgan hemorrhoidectomy in terms of safety and efficacy. Methods: This study was performed after the approval of the ethics committee of review board of Maharashtra University of Health Sciences during the period May 2010-2012 on patients of grade 3 and 4 hemorrhoids. 60 patients were included in the study after giving written consent. They were divided into two groups consisting 30 in each and conventional hemorrhoidectomy or vessel sealing technique hemorrhoidectomy was performed respectively. The demographic data, duration of surgery, blood loss during surgery, intraoperative and postoperative complications, postoperative pain, initiation of bowel movement and in hospital stay were evaluated. The postoperative pain was evaluated with the visual analogue score (VAS) after surgery. Results: The mean operative time, blood loss, pain score and requirement of analgesia was significantly (p <0.05) higher in patients treated with conventional Milligan Morgan hemorrhoidectomy (MMH) compared to vessel sealing (VS) method. The time for first bowel movement, length of hospital stay was longer in MMH group compared to VS group. The ability of patient to return to normal activities had taken significantly (p <0.05) longer time in patients operated with conventional method compared to VS method. Experience of early and late complications after surgery in two groups was comparable but the difference was not significant. Conclusions: Vessel sealing technique for hemorrhoidectomy is a feasible and time saving technique for the surgeon and a comfortable procedure for the patient